PENGGUNAAN METODE DISKUSI UNTUK MENINGKATKAN AKTIVITAS SISWA DALAM PEMBELAJARAN ILMU PENGETAHUAN SOSIAL (IPS) KELAS V SDN NO.14 OYAH KIRI KECAMATAN MENUKUNG - Maharan Maharan; Andi Usman; Yakobus Ason (JURNAL PENDIDIKAN DASAR, 2014)
The purpose of this research is to increase the student learning activity of the subject social science by using the discussion method. The research was taken over 15 students of grade V, public elementary school No.14 Oyah Kiri, Menukung District. In order to reach that purpose, the researcher did research action in class through 2 cycles. There was significant increase from the first cycle to the second cycle. First, the student activity in learning social science increased for about 11.27% in the first cycle. Second, the student activity in learning social science increased for about 21.26% from the first cycle to the second cycle. Therefore, the student activity in learning social science was increased for about 32.53%.Key words: The Increasing Learning Activity, Social Science Subject